DEVELOPING POP-UP BOOK TO TEACH VOCABULARY FOR SEVENTH GRADE STUDENTS OF MTS SIROJUT THOLIBIIN - Dewi Rahmawati; Tyas Alhim Mubarok; Siti Rofi’ah (PROJECT (Professional Journal of English Education), 2023)
This research and development aimed to represent the process and results of developing pop-up book media for teaching vocabulary in descriptive text material. The research subject was 28 students of VII-A grade at MTs Sirojut Tholibiin. The development procedure referred to ADDIE model. Observation, questionnaire and interview techniques were used as information gathering in preliminary study. Meanwhile, to decide the feasibility of pop-up book product, researchers used questionnaire instrument given to content and media experts. Then, the student response questionnaire to find out the level of student satisfaction with media. According to the assessment of content expert, it obtained score of 92% which had very good category. From media expert, it achieved score of 75% which was classified in good category. Furthermore, the result of student response questionnaire also got score of 75% in good category. Based on the overall assessment, the development of pop-up book learning media on descriptive text material with animal themes for seventh grade was declared feasible and suitable to be used in teaching and learning activities. Keywords:  ADDIE Model; Descriptive Text; Pop-up Book